Integrating Modern Cassava Processing And Digital Marketing To Strengthen Local Businesses In Angat Buhay Village, Philippines - Indiani, Ni Luh Putu; Mangku, I Gede Pasek; Putra, I.B. Udayana; Sumayo, Romeo M.; Lestari, Ni Luh Metri; Wibawa, I Made Aryan Satriya; Darmawan, Kadek Dinda Rahayu (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This international community service program was carried out in Angat Buhay Village, Philippines, with the aim of increasing community capacity in cassava processing and digital marketing. The main problem of partners is the limited skills of food technology, production facilities, and offline and digital marketing. The solutions provided include training in cassava processing (mocaf and chips), the provision of modern tools (graters, dryers, vacuum sealers), as well as training in digital marketing strategies through social media and marketplaces. The results of the activity show an increase in the production capacity of partners, partners to produce new products (mocaf and chips), partners have social media, and an increase in sales through digital channels. The program also strengthens international academic collaboration (Warmadewa - UNC).